Voluntary exercise may engage proteasome function to benefit the brain after trauma - Szabo, Zsofia (2009)
Brain trauma is associated with long-term decrements in synaptic plasticity and cognitive function, which likely reside on the acute effects of the injury on protein structure and function. Based on the action of proteasome on protein synthesis and degradation we have examined the effects of brain injury on proteasome level/activity and the potential of exercise to interact with the effects of the injury. Exercise has a healing ability but its action on proteasome function is not understood. Male Sprague-Dawley adult rats (n=19) were performed mild brain fluid percussion injury (FPI) prior to exercise. Animals were assigned to four groups: sedentary (Sed) or exercise (Exc) with sham surgery (Sham) or FPI: Sham/Sed, Sham/Exc, FPI/Sed, FPI/Exc. Animals were sacrificed after 14 days of treatment. FPI elevated levels of carbonyl (160.1±9.6% SEM, p<0.01) and reduced synapsin I levels (58.3±4.3% SEM, p<0.01) in the ipsilateral side of caudal cerebral cortex (FPI/Sed compared to Sham/Sed controls), and it appears that increased levels of carbonyls were associated with increased chymotripsin like activity. These results seem to indicate that proteasome function may be associated with levels of oxidative stress, and that these events may contribute to the action of exercise on synaptic plasticity. Interestingly, exercise attenuated changes in carbonyls, proteasome activity, and synapsin I following FPI, which may indicate an action of exercise on the molecular substrates that control protein turnover following brain trauma. Levels of the regulatory transcription factor of proteasome, Zif 268 were reduced by exercise in Sham and FPI animals and changed in proportion with proteasome activity/content. The overall results indicate that the action of exercise interfaces with that of brain injury on molecular systems involved with protein fate and function, which may be significant for synaptic plasticity.